How do dismissal laws affect firm profitability? - Gama, Miguel Yum (2013)
The purpose of this dissertation is to study whether and to what extent dismissal laws affect firm profitability. To achieve this goal, a within-country analysis was conducted into U.S. firms that were affected by the passage of the federal Worker Adjustment and Retraining Notification Act of 1989 (the WARN Act) in the years between 1980 and 2000. The results show that the introduction of such dismissal law had a positive and statistically significant impact on firm profitability. Furthermore, this effect was particularly pronounced for those firms that invested in R&D expenditure.